2008
DOI: 10.1073/pnas.0805044105
|View full text |Cite
|
Sign up to set email alerts
|

The redox activity of ERp57 is not essential for its functions in MHC class I peptide loading

Abstract: ERp57 is an oxidoreductase that, in conjunction with calnexin and calreticulin, assists disulfide bond formation in folding glycoproteins. ERp57 also forms a mixed disulfide with the MHC class I-specific chaperone tapasin, and this dimeric conjugate edits the peptide repertoire bound by MHC class I molecules. In cells unable to form the conjugate, because of tapasin mutation in human studies or ERp57 deletion in mouse studies, peptide loading is impeded. Subtle differences between the mouse and human systems h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…1). The tapasin-ERp57 complex already highlights the capability of ERp57 to act in different ways, since, contrary to its participation in glycoprotein folding, calreticulin does not constitute an absolute requirement [32], and the redox activity of ERp57 is not involved in the assembly of the peptide loading complex [32,33] except for the formation of a stable disulfide bond between cys-57 of ERp57 and cys-95 of tapasin. Actually a function of this strong complex seems to be the inhibition of the reduction of the disulfide bonds of the heavy chains, which are required for the proper formation of the MHC.…”
Section: Erp57 In the Endoplasmic Reticulummentioning
confidence: 99%
“…1). The tapasin-ERp57 complex already highlights the capability of ERp57 to act in different ways, since, contrary to its participation in glycoprotein folding, calreticulin does not constitute an absolute requirement [32], and the redox activity of ERp57 is not involved in the assembly of the peptide loading complex [32,33] except for the formation of a stable disulfide bond between cys-57 of ERp57 and cys-95 of tapasin. Actually a function of this strong complex seems to be the inhibition of the reduction of the disulfide bonds of the heavy chains, which are required for the proper formation of the MHC.…”
Section: Erp57 In the Endoplasmic Reticulummentioning
confidence: 99%
“…Ataxin 324-333 (QVFPGLLERV) was modified with substitutions of F to Y, and R to K, resulting in the QVY peptide, QVYPGLLEKV. Ribosomal protein L10a [8][9][10][11][12][13][14][15][16] (TLYEAVREV) was modified with substitution of E to K, resulting in the TLY peptide, TLYEAVRKV. Cadherin 17 precursor 2-10 (ILQAHLHSL) was modified with substitutions of Q to Y, and of S to K, resulting in the ILY peptide, ILYAHLHKL.…”
Section: Peptidesmentioning
confidence: 99%
“…Since its discovery, tapasin has been attributed several functions -to increase the available local peptide concentration by bridging HLA-I molecules to TAP [2][3][4], to stabilize TAP expression and improve its capacity to bind peptide prior to the translocation step [5][6][7][8], to keep HLA-I molecules peptide-receptive in the PLC [9][10][11], to recycle empty or suboptimally loaded HLA-I molecules back to the ER [4,[12][13][14], and, to act as a peptide-editor, allowing exchange of suboptimal peptides for optimal peptides [1,15,16]. However, the exact molecular mechanisms of the tapasin-mediated HLA-I quality control remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While this manuscript was in preparation, Cresswell and coworkers (49) reported that when the C60A/C406A/C409A mutant of human ERp57 was expressed in cells stably knocked down for endogenous ERp57, it fully supported PLC assembly and the generation of stable, peptide-loaded human HLA*B4402 molecules. Although consistent with our findings in the mouse system, the interpretation of their results is complicated by the presence of residual conjugate between tapasin and endogenous wild type ERp57 that remained following the ERp57 knockdown.…”
mentioning
confidence: 99%